ANALYSIS OF HUMOR IN THE BIG BANG THEORY BY USING RELEVANCE THEORY: A PRAGMATIC STUDY - Lilis Ade Sartika; Budi Eko Pranoto (Linguistics and Literature Students' Journal, 2021)
Humor has been studied from different disciplinary viewpoints including philosophy, psychology, sociology, literature, rhetoric, linguistic and others by many scholars and experts. Thus, with the development of humor study, the linguistic perspective is becoming the mainstream of thoughts because it is more applicable and more systematic. In that case, to understand the pattern of communication in humor, the study of pragmatic is needed. Therefore, this research is aimed to analyze humor that are produced in The Big Bang Theory (a famous sitcom in America) from the perspective of cognition and communication. The analysis is done by applying descriptive method and using Sperber and Wilson’s theory of relevance theory. As the result of the analysis, it shows that there is a lot of humors that are based on relevance communication so that the application of relevance theory must be applied in order to understand the context of the humor. Further, the writer also noticed that the form of verbal humor used in The Big Bang Theory mostly showing about common problems and drama situation such friendship, job and daily life. In addition, regarding to the relevance theory of communication, the writer also noticed that the mechanism of humor in The Big Bang Theory is using the moment of optimal relevance of cognitive principle which means that when the audience has a common presumption of a context of conversation, the speaker or the characters in the sitcom is producing or uttering something unexpected in order to make the audience laugh or joy in humor.Keywords: context of humor, humor, pragmatic, relevance theory